PENGARUH SOSIAL NETWORK MARKETING TERHADAP CUSTOMER PURCHASE INTENTION YANG DIMEDIASI OLEH CUSTOMER ENGAGEMENT PADA BRAND DIAN PELANGI DI BANDA ACEH - Hajrina Ulfah; Muhammad Ridha Siregar (Jurnal Manajemen Inovasi, 2019)
Abstract This research wad conducted to measure the influence of Social Network Marketing on Customer Purchase Intention with Customer Engagement as a mediation variable at Brand Dian Pelangi in Banda Aceh. The sample used in this study is the citizen of Banda Aceh who use social network application with the total of 110 respondents. The data collecting tool used in this research is questionnaire. Purposive sampling method is used for the sampling technique of this research. Hierarchical Linear Modeling (HLM) is used as an analytical method to determine the effect of all the variables involved.Based on the result of  the HLM analysis, it indicates that Social Network Marketing has positive effect on Customer Purchase Intention, Social Network Marketing has positive influence on Customer Engagement, Customer Engagement has positive effect on Customer Purchase Intention, and, Customer Engagement mediates Social Network Marketing relationship to Customer Purchase Intention KeywordsSocial Network Marketing, Customer Purchase Intention, Customer Engagement, Hierarchical Linear Modelling